2019
DOI: 10.1136/inp.l1626
|View full text |Cite
|
Sign up to set email alerts
|

Handling and storing medicines on beef and dairy farms

Abstract: Veterinary medicines that are stored on the majority of UK farms include antimicrobials, anthelmintics, non-steroidal anti-inflammatory drugs and vaccines. All prescription veterinary medicines have storage requirements as directed on the datasheet or summary of product characteristics (SPC) and there are also specific instructions for how, when and where medicines should be administered. Vaccines often have storage and handling instructions on the SPC in addition to those applied to other medications; most al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…These ndings are different to those of Cresswell et al (2019) who found over 27% of farmers administered antibiotics via incorrect routes, although the reasoning behind these difference cannot be con rmed the importance of the RVM in providing an annual refresher in medicine administration cannot be overlooked. Interestingly, although none of the farmers interviewed in this study knew the full rationale behind application methods, all were able to make reference to why it had to be done a speci c way, moreover all farmers expressed the importance of a dose rate again a difference found to those of (Cresswell et al, 2019).…”
Section: Discussionmentioning
confidence: 94%
“…These ndings are different to those of Cresswell et al (2019) who found over 27% of farmers administered antibiotics via incorrect routes, although the reasoning behind these difference cannot be con rmed the importance of the RVM in providing an annual refresher in medicine administration cannot be overlooked. Interestingly, although none of the farmers interviewed in this study knew the full rationale behind application methods, all were able to make reference to why it had to be done a speci c way, moreover all farmers expressed the importance of a dose rate again a difference found to those of (Cresswell et al, 2019).…”
Section: Discussionmentioning
confidence: 94%